Seepage Characterization Based on Sandstone Particle Motion Pattern: A Case Study of the TIII Reservoir in the Sangtamu Oilfield - Lyu Duanchuan; Wang Rujun; Wang Xixin; Wang Chao; Zhu Zhengjun; Wang Kaiyu; Lou Hong; Wang Xiaoming; Song Jinpeng (Geofluids)
In order to finely characterize the physical properties and seepage characteristics of underwater distributary channel sand bodies in a braided river delta, the particle size distribution, mercury injection, and withdrawal of low, medium, high, and extra-high permeability core samples from the TIII reservoir from 15 core wells in the Sangtamu Oilfield were compared. The pore-throat characteristics of the rocks with different deposition modes and their effects on the fluid seepage were analyzed from the perspective of the deposition processes. The statistical results revealed that the rocks formed in a continuous and stable strong hydrodynamic environment were coarse grained. The seepage capacities of the rock increased as the maximum throat radius connecting with the pores increased. The mercury withdrawal efficiency decreased as the difference between the throat radius and pore radius increased. The percentage of the throat volume without effective seepage to the total volume of the pore-throat system increased as the permeability of the samples increased. Therefore, when characterizing reservoirs based on the porosity and permeability, it is important to differentiate the energy of the hydrodynamic depositional environment of a monogenic sand body in order to improve the accuracy of the understanding of the reservoirs.